Diversidad y actividad horaria de mamíferos medianos y grandes registrados con cámaras trampa en el Parque Nacional Tingo María, Huánuco, Perú - Cossios, E. Daniel (2019)
The mammal fauna of the Parque Nacional Tingo María (PNTM) mainly is known for local people interviews. In this work, using camera traps and its verification by interviews to local people we report medium and large mammals list of the PNTM. Evaluations were realized between December 2014 and November 2018. Sampling effort was of 2970 camera traps/day, with 1640 independent records. Nineteen wild species were recorded, four of which were new reports to the PNTM (the water opossum Chironectes minimus, the margay Leopardus wiedii, the Northern tiger cat Leopardus tigrinus and the crab-eating raccoon Procyon cancrivorus), three were new reports for the Peruvian yungas (L. wiedii, the capybara Hydrochoerus hydrochaeris and the Neotropical otter Lontra longicaudis) and two (H. hydrochaeris and L. wiedii) have been registered as its higher altitude record in Peru. Activity patterns were elaborated for the nine species with more than 10 records. Eight of them are coincided with the previously published. Activity pattern of pacarana (Dynomis branicki) is the first one elaborated in wild conditions. The presence of several predator species and normal activity patterns, would be suggest a good state of forest conservation in the PNTM. In conclusion, the sampling using camera traps allow to obtain a reliable and fairly complete list of the medium and large terrestrial mammals of the PNTM, as well as data on their distribution and ecology.